The Photosystem II Subunit S under Stress - Daskalakis, Vangelis; Papadatos, Sotiris (My University, 2017)
Nonphotochemical quenching is the protective mechanism against overexcitation of photosystem II, triggered by excess ΔpH in photosynthetic membranes. The light-harvesting complexes (LHCs), the de-epoxidation of violaxanthin to zeaxanthin, and the photosystem II subunit S (PsbS) work in synergy for an optimized multilevel response. Understanding the fine details of this synergy has proven challenging to scientific research. Here, we employ large-scale, all-atom molecular simulations and beyond experimental insight, we proceed a step further in identifying the PsbS dynamics that could possibly be associated with this synergy. For the first time, to our knowledge, we probe the distinct behavior of PsbS under ΔpH that probes the details of the potential dimer-to-monomer transition, and in a violaxanthin/zeaxanthin-rich membrane, at an all-atom resolution. We propose that the lumen-exposed residues, threonine 162 and glutamic acid 173, form stabilizing hydrogen bonds between the PsbS monomers only at high lumen pH, whereas at low pH (excess ΔpH) this interaction is lost, and leads to higher flexibility of the protein and potentially to the dimer-to-monomer transition. Lastly, we discuss how conformational changes under the presence of ΔpH/zeaxanthin are related to the PsbS role in the current nonphotochemical quenching model in the literature. For the latter, we probe a PsbS-monomeric LHCII association. The association is proposed to potentially alter the monomeric LHCII sensitivity to ΔpH by changing the pKa values of interacting LHCII residues. This serves as an example where protonation-ligation events enhance protein-protein interactions fundamental to many life processes.
Keywords: Xanthophyll; Chemistry; Protein multimerization; Protein quaternary structure